WHICH IS MORE EFFECTIVE IN REDUCING BLOOD PRESSURE IN HYPERTENSION PATIENTS: A LOW SALT DIET OR THE DIETARY APPROACHES TO STOP HYPERTENSION (DASH)? - Vidhiastutik, Yusiana; Peristiowati, Yuly (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2024)
Background: Hypertension is a disease that requires early attention. One effort to prevent increased blood pressure in hypertension sufferers is to implement a diet that has been consulted with nutrition experts. Objectives: The aim of preparing this literature review is to compare the effectiveness of implementing a low-salt diet and dietary approaches to stop hypertension from the results of previous research. Design: The design used in preparing this article is a systematic review. Data Sources: This systematic review used 5 search databases to collect articles, including SCOPUS, Pubmed, Google Scholar, DOAJ, and ScienceDirect with the search year range 2019-2024. Review Methods: The researchers used the JBI Critical Appraisal guidelines to determine articles suitable for this systematic review. Then, the selected articles were reviewed comprehensively using a narrative approach. Results: Search results obtained 10,685 publications. Researchers filtered by eliminating duplicate publications, reviewing articles, and focusing on the Issue of Interest in Table 1 totaling 9,578 publications. Researchers re-screened the title (n = 598), abstract (n = 387), and full text (n = 113) of each publication that did not meet the inclusion criteria in Table 1. The researchers found 9 full-text publications that met the requirements for use in this systematic review. However, researchers only used 7 publications because 2 publications were considered to have a risk of bias. Conclusion: Based on the results of a systematic review that has been carried out, it was found that implementing the DASH diet will be more effective than implementing a low-salt diet.